On missional medicine: institution building, fragile places, and sheep among wolves - C. Phifer Nicholson; Bruce Dahlman; Martha C. Carlough (Christian Journal for Global Health, 2023)
From the healing narratives of Jesus in the Gospels to the genesis of the first hospital to the practice of modern medicine, questions surrounding health and care for those who are sick and dying run through the heart of the Christian story. One way that individuals and communities have sought to live into their faith has been through missional medicine, that is, seeking to intentionally use the tools of medicine in step with and to bear witness to the life of Christ, particularly in crosscultural and global contexts. In this commentary, we take up the incisive question of the late missionary physician Raymond Downing, “is there a distinctive Christian approach to global health?” Or, what sets (and should set) Christian approaches to global health apart from other interventions? Here, we argue that there are at least three distinctive Christian contributions to global health. First, missional medicine movements have been committed to the building of long-standing hospitals and academic medical institutions that have left indelible marks on long-term health outcomes for people and communities. Second, practitioners motivated by Christian convictions disproportionately serve and remain long-term in marginalized, rural, and underserved areas; many of which are connected to fragile or under-developed health systems. Thirdly, Christian medical missionaries and global health workers ought to be, in the words of Jacques Ellul: preserving salt, revealing light, and “sheep in the midst of wolves.” This is a theologically framed vocation that accepts suffering and sacrifice, embracing solidarity through accompaniment. This paper is not meant to be a comprehensive history of missional medicine nor a defence of its problematic manifestations over the centuries. Rather, we candidly explore examples of the distinctive contributions that have been made, and we hope will continue to be made, by medical missionaries and global health workers who are motivated by their faith.